2019
DOI: 10.1021/acsami.9b02233
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Ferroelectret Polymer for Self-Powering Devices and Energy Storage Systems

Abstract: Applying flexible materials for energy scavenging from ambient mechanical vibrations is a clean energy solution that can help alleviate electrical power demands in portable devices and wearable electronics. This work presents fundamental studies on a flexible ferroelectret polymer with a strong piezoelectric effect and its interface with self-powered and energy storage systems. A single-layered device with a thickness of 80 μm was used for characterizing the device’s output voltage, current, transferred charge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 50 publications
(59 reference statements)
1
16
0
Order By: Relevance
“…In this study, a flexible polypropylene-based FENG device reported in our previous work is used as the tactile transducer due to its high efficiency and biocompatibility, as shown in Figure 6a. 47 A mechanical input (displacement, force, pressure) generates dipole moments across polypropylene's thickness, creating an electric field that is compensated by the accumulation of charge of opposite polarities at both surfaces of the material. This charge can be collected through thin metal film contacts on the polymer surface, resulting in a small electrical current that is proportional to the rate of change in the applied mechanical input, and flows in opposite directions depending on the direction of the input cycle (e.g., compression/ relaxation).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, a flexible polypropylene-based FENG device reported in our previous work is used as the tactile transducer due to its high efficiency and biocompatibility, as shown in Figure 6a. 47 A mechanical input (displacement, force, pressure) generates dipole moments across polypropylene's thickness, creating an electric field that is compensated by the accumulation of charge of opposite polarities at both surfaces of the material. This charge can be collected through thin metal film contacts on the polymer surface, resulting in a small electrical current that is proportional to the rate of change in the applied mechanical input, and flows in opposite directions depending on the direction of the input cycle (e.g., compression/ relaxation).…”
Section: Resultsmentioning
confidence: 99%
“…Flexible tactile transducers such as triboelectric nanogenerator or ferroelectret nanogenerator can be readily used to convert external force stimulus to a pulsed electrical signal without the need for a power supply, and they exhibit behaviors that closely resemble skin mechanoreceptors. In this study, a flexible polypropylene-based FENG device reported in our previous work is used as the tactile transducer due to its high efficiency and biocompatibility, as shown in Figure a . A mechanical input (displacement, force, pressure) generates dipole moments across polypropylene’s thickness, creating an electric field that is compensated by the accumulation of charge of opposite polarities at both surfaces of the material.…”
Section: Results and Discussionmentioning
confidence: 99%
“…When a large electric field is applied across the film, gas molecules in the cells become ionized and opposite charges are accelerated and implanted on each side of the cells, depending on the applied electric field direction [39][40][41]. Such artificially embedded dipoles respond externally to an applied electrical field or mechanical force similar to piezoelectric material [42]. Porous piezoelectric polymers are also extremely flexible, making them ideal candidates for mechanical energy harvesters [43].…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al [25], investigated the optimal configuration for multi-renewable energy systems and considered load profiles, energy prices, and equipment parameters to create optimal consideration systems; the proposed approach can optimize both the equipment selection and the configuration of the multi-energy system. Cao et al [26] studied polypropylene ferroelectric (PPFE) as nanogenerators that can convert mechanical energy to electrical energy for self-powering devices and energy storage systems; the maximum power output obtained around 0.902 µW. This technique can be used for powering electronic devices and a solid-state battery chip.…”
Section: Introductionmentioning
confidence: 99%